Paradoxal produção científica na pandemia : 1 ensaio clínico randomizado e 40 artigos - Baron, Miriam Viviane (2022)
This thesis comprises two chapters: 1) Neuromuscular electrical stimulation in the prevention of pressure injury in the posterior region of the pelvis of patients admitted to the Intensive Care Unit: a randomized controlled clinical trial of efficacy and safety; 2) Cientific production performed during the social isolation imposed by the pandemic. Chapter 1 - Pressure injury (PI), especially in the posterior region of the pelvis, in patients in the Intensive Care Unit (ICU) is frequent, costly and increases morbidity and mortality. These injuries can occur from prolonged pressure and/or shear forces. Neuromuscular electrical stimulation (NMES) is proposed to improve local circulation and pressure relief, reducing the incidence of PI. A randomized and controlled clinical trial was carried out to evaluate the efficacy and safety of NMEE in preventing PI in critically ill patients. Patients with an ICU stay of less than 48 hours, older than 18 years and without PI were included. Participants were randomly selected (1:1 ratio) to receive NMEE and usual care (NMEE group - NMEEG) or only usual care (control group - CG) until discharge, death, withdrawal or onset of PI. Efficacy of NMEE was calculated by relative risk (RR), relative risk reduction (RRR), absolute risk reduction (RRA) and number needed to treat (NNT). Muscle thickness and the presence of edema in the skin layers were evaluated by ultrasonography. Safety was assessed by the effects on mean arterial pressure, heart and respiratory rates, peripheral oxygen saturation (SPO2) and the incidence of burns caused by NMES. 149 participants were selected, 73 in the CG and 76 in the NMEEG. PI was present in 26 (35.6%) patients in the CG and in 4 (5.3%) in the NMEEG (p˂0.001). The NMEEG presented an RR = 0.15 (95% CI: 0.05-0.40), RRR = 85.1% (95% CI: 60-95), RAR = 30.3 (95% CI: 16 .9-43.5), NNT = 3.3 (95% CI: 2.3-5.9). There was no statistical difference between groups in gluteal muscle thickness between the 1st and 7th day. Ultrasonography showed deep edema in the mid-sacral crest region in the first 48 hours and on the 7th day. NMEE did not promote deleterious alterations in any evaluated safety parameter. It was concluded that NMEE is an effective and safe therapy for the prevention of PI in critically ill patients. Chapter 2 - The pandemic interrupted the normal course of daily life. Researchers not related to the COVID-19 theme were suspended until further notice. With the doctorate taking place outside the University, it was decided to produce articles that did not require the experimental part. This chapter brings the scientific production made during the pandemic period with the internet support that coincided with the doctoral period – almost two years. The variety of subjects in the articles and of collaborators, both from the institution itself and externally, as well as nationally and internationally, is noteworthy. The decision to continue producing, when in a domestic environment, was, besides being inspired by the research, a form of retribution to CAPES for maintaining the scholarship during the pandemic period.